HUBUNGAN ANTARA STIGMA DENGAN INTERAKSI SOSIAL ORANG DENGAN HIV DAN AIDS (ODHA) DI KELOMPOK DUKUNGAN SEBAYA (KDS) DELI SERDANG - Meliala, Sinarsi; Nursiti, Dwi; Ningsihi, Siska Dwi; Telaumbanua, Elvi Putri Jaya (JURNAL PSYCHOMUTIARA, 2022)
Cases of HIV / AIDS have increased and so far no cure has been found and is a deadly disease. The cause is due to factors of unhealthy sexual behavior, transmission of syringes, and blood transfusions done in the wrong way. Stigma is one of the psychosocial problems in people with HIV / AIDS which causes a negative impact because it can affect the interaction process in the community. This research was conducted with the title of the relationship between stigma and social interaction of people with HIV and AIDS (PLWHA) in a social support group. This research was conducted in Deli Serdang Regency in a social support group with a total sample of 36 people with a population of no more than 50 people. The sampling technique used is total sampling. The research was conducted using a quantitative approach. Data collection techniques using a questionnaire with a Likert scale model. The results showed that there was a relationship between stigma and social interaction among PLWHA with high correlation categorization